Are health care scams infectious? Empirical evidence on contagion in health care fraud - Rajeev K. Goel (Managerial and Decision Economics, 2020)
This paper examines the presence of contagion in health care fraud across jurisdictional boundaries. Using state-level data for the United States, we find evidence of contagion in medical fraud. There are also spillovers from border corruption on medical fraud, but no evidence of spillovers from international borders. In other findings, greater urbanization, greater elderly population, and higher hospital occupancy positively contribute to medical fraud, while nursing employment has a mitigating effect. Further, it is economic inequality rather than economic prosperity that seems relevant. The main findings are robust to consideration of simultaneity, but dependent upon the prevalence of fraud across states.
Keywords: 650